Cultivating Pathways to Nature Connection Through Collaborative Music Creation: A Workshop Model - Qinthar Qibran Kurniawan; Denis Setiaji (Jurnal Multidisiplin Sahombu, 2026)
This research explores the emergence and transformation of nature connection pathways into collaborative music by designing and implementing a nature-based collaborative music creation workshop model. Employing a practice-based approach, the study integrates four theoretical frameworks, including the Five Pathways to Nature Connection (FPNC), the Soundtalking method, Collaboration Principles, and the Music Paradigm of Creativity. The resulting three-stage model (pre-creation, collaborative creation, and post-creation) was implemented over five weeks with ten participants (aged 15-22 yearts) at the Sekolah Seni Tubaba. Data from field notes, focus group discussions, and multimodal documentation were analyzed abductively and iteratively. Findings indicate that pathways to nature connection (FPNC) can be cultivated and strengthened through nature’s sound exploration, collaborative music-making, and reflective dialogue. The analysis also produced a collaborative information-processing model that elucidates how shared understanding of nature is transformed into artistic work. The creation of two musical compositions, "Mulai Bernapas" and "Rahim Alam," proves that collaborative artistic practice can serve as an epistemological site for forming, deepening, and expanding nature connection pathways.